1967
DOI: 10.2135/cropsci1967.0011183x000700060026x
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and Combining Ability in Barley1

Abstract: Eight parental varieties of barley and the 28 possible F1 and F1 populations were evaluated in spaced plantings in two environments. The traits studied were yield, kernel weight, kernels per head, heads per plant, and height.The average heterosis values of F1's based on midparent means for yield, kernel weight, kernels per head, heads per plant, and height were 21.5, 5.9, 7.1, 7.6, and 3.2%, respectively. When the F1's were compared to the high parent, the average heterosis for yield was 9.1%. The average inbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1971
1971
2002
2002

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…The results were not as promising as those reported by This supports the finding that the hybrids responded difierently in the two environments. (12) and in wheat (I,7).…”
Section: Discussionmentioning
confidence: 99%
“…The results were not as promising as those reported by This supports the finding that the hybrids responded difierently in the two environments. (12) and in wheat (I,7).…”
Section: Discussionmentioning
confidence: 99%
“…Carleton and Foote (1968) did not find heterosisi for yield or for leaf area in tworow by six-row crosses, even though the parents differed reciprocally for components of yield and for components of leaf area. Upadhyaya and Rasmusson (1967) also found some hybrids that exhibited no heterosis for yield, even though the parents differed reciprocally for the components of yield. However, they did find several hybrids that exhibited heterosis which involved parents that showed reciprocal differences in yield components, as well as hybrids that exhibited heterosis from crosses where the parental varieties did not differ reciprocally for the components of yield.…”
Section: Base Of Heterosis In Barleymentioning
confidence: 94%
“…Gustafsson and Dormling (1972) reported heterosis arising from interaction between maturity alleles at one locus, overdominance, in barley grown in a growth chamber, while Aastveit (1964) reported that heterosis found in the F 1 was ,based on non-allelic interactions and could be fIxed in true breeding form. Upadhyaya and Rasmusson (1967) reported data concerning heterosis and combining ability in the 28 F 1 and F 2 populations obtained from crossing 8 parental varieties in all possible combinations. They stated that a substantial amount of additive and non-additive genetic variance for yield was indicated.…”
Section: Base Of Heterosis In Barleymentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately reports have sometimes been based on 'heterosis' relative to mid-parent values, using spaceplanted seeds, where the extra tillering capacity of the F 1 plant shows to advantage, which it does not do under normal agricultural conditions [66,140]. Thus large-scale agricultural trials are indispensable for evaluating this idea [131,158]. In one set of trials heterosis for forage was from 8 to 31% and for grain yields, 8-37%.…”
Section: 'Hybrid' Barleymentioning
confidence: 99%